A Theory of coalition Bargaining - Yves Breitmoser (European University Viadrina, Department of Business Administration and Economics, 2006)
When voting takes place in democratic institutions, we find (either explicitly or implicitly) that there is an agenda setter or a formateur. Such players are uniquely able to make substantive proposals for given topics. Their statuses remain intact even after rejection of proposals, but they must revise rejected proposals constructively (e.g. towards a compromise). We model this in a general environment, show that the equilibrium outcome is generically unique, and characterize it explicitely. The equilibrium outcome is robust to (partially) binding communication between the formateur and the voters. As illustrations, we consider majority bargaining about a cake (leaned on Baron and Ferejohn,1989),where the formateur ends up being a perfect dictator, and a model of legislative voting (leaned on Jackson and Moselle,2002), where he is a dictator if his ideological position is within the quartiles of the parliament. In these cases, our model implements (reversed) McKelvey majority path. Depending on the valuations, the formateurs power may be weakened when parliamentary decisions can be revised, as this may faciliate tacit collusion amongst the voters.
Keywords: C78; C72; D72; 330; coalitional bargaining; legislature; non-cooperative